The Long-Run Effects of Cesarean Sections - Ana María Costa-Ramón; Mika Kortelainen; Ana Rodríguez-González; Lauri Sääksvuori (University of Wisconsin Press, 2025)
This paper analyzes the long-term effects of potentially avoidable  C-sections on children's health. Using Finnish administrative data, we document that physicians perform more unplanned C-sections during their regular working hours on days that precede a weekend or public holiday and use this exogenous variation as an instrument for C-sections. We supplement our instrumental variables results with a differences-in-differences estimation that exploits variation in birth mode within sibling pairs and across families. Our results suggest that avoidable unplanned C-sections increase the risk of asthma, but do not affect other immune-mediated disorders previously associated with C-sections.